Teachers 'Professionality in Improving the Quality of Madrasah Education in The Era of Globalization - Hasperi Susanto; Rambat Nur Sasongko; Muhammad Kristiawan (Universitas Cokroaminoto Palopo, 2021)
The research objective was to determine and describe the quality of madrasah education in the study of teacher professionalism in the era of globalization. The method uses a qualitative approach with the type of library research (library research) and data sources from books and journals about the quality of madrasah education and the professionalism of teachers in the era of globalization. The results of this study indicate that the quality of madrasah education in the era of globalization in the 21st century in the western, eastern and central parts of Indonesia has a difference in the quality of quality education in accordance with the National Education Standards (SNP). Teacher professionalism is one of the main factors affecting the quality of education. Professional teachers must have the ability to: master teaching materials and materials; master and apply philosophy, methods, techniques and practices; take advantage of ICT developments to improve the quality of learning; self and develop professional performance; and increase commitment to dedication in society.